1998
DOI: 10.1046/j.1365-2133.1998.02186.x
|View full text |Cite
|
Sign up to set email alerts
|

Porokeratotic eccrine ostial and dermal duct naevus with dermatomal trunk involvement: literature review and report on the efficacy of laser treatment

Abstract: Porokeratotic eccrine ostial and dermal duct naevus (PEODDN) is a rare, benign hamartomatous malformation involving the eccrine sweat duct. The existence of filiform keratinous plugs that represent cornoid lamellae overlying dilated infundibula of eccrine ducts is a distinctive feature and the presence of associated abnormal dermal ducts is frequent. We report a patient with PEODDN who exhibited lesions on the left side of her chest. Cases of PEODDN reported in the literature are reviewed. Our experience in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…It has been suggested that involvement of the epidermis with sparing of the adnexa may be used as a criterion in favor of a diagnosis of linear porokeratosis. 9,21 As several biopsies and multiple sections may be needed to differentiate linear porokeratosis and PAON, cases of PAON may have been missed because of an apparent lack of eccrine duct involvement. In addition, cornoid lamellae are well known to occur over adnexa in conventional porokeratosis.…”
Section: Clinical Differential Diagnosismentioning
confidence: 98%
See 4 more Smart Citations
“…It has been suggested that involvement of the epidermis with sparing of the adnexa may be used as a criterion in favor of a diagnosis of linear porokeratosis. 9,21 As several biopsies and multiple sections may be needed to differentiate linear porokeratosis and PAON, cases of PAON may have been missed because of an apparent lack of eccrine duct involvement. In addition, cornoid lamellae are well known to occur over adnexa in conventional porokeratosis.…”
Section: Clinical Differential Diagnosismentioning
confidence: 98%
“…The ultrapulsed carbon-dioxide laser has been used, but multiple treatments may be required 22 and the papules may recur. 21 Simple surgical excision should be reserved for cases with limited involvement, and the plaques can recur despite excision. 7 Topical corticosteroids, calcipotriol ointment, phototherapy, and cryotherapy have proven ineffective.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations